ANALISIS PUTUSAN NOMOR 1008/PID.SUS/2023/PN SBY TENTANG PEMIDANAAN TERHADAP PELAKU PENYALAHGUNA NARKOTIKA GOLONGAN I UNTUK DIKONSUMSI SENDIRI: Analysis Of Decision Number 1008/Pid.Sus/2023/Pn Sby ​Concerning The Punishment Of The Perpetrators Of Class I Narcotics Abuse For Their Consumption - Rizkiati Neneng Hasanah; Sutrisno (Faculty of Law, Universitas Trisakti, 2025)
Cases of drug abuse are increasing in Indonesia, but the handling is still not optimal, including the legal process in court. This research will examine Decision Number 1008/Pid.Sus/2023/PN Sby in relation to Supreme Court Circular Letter (SEMA) Number 4 of 2010 concerning the Placement of Narcotics Abuse, Abuse Victims and Addicts into Medical Rehabilitation and Social Rehabilitation Institutions. Based on this decision, the defendant was imprisoned for 2 years and 6 months. The problem studied is whether the application of sanctions against class I narcotics abusers in Decision Number 1008/Pid.Sus/2023/PN Sby is in accordance with the principles of punishment. This research is normative legal research with descriptive analytical analysis of secondary data, using a qualitative approach and deductive method in concluding. The results of the discussion and conclusions reveal that the decision is not in line with the purpose of punishment, because the panel of judges inappropriately applied Article 127 of Law Number 35 of 2009 concerning Narcotics. Class I drug abusers for personal use should receive medical and social rehabilitation, not criminal punishment as stipulated in the law and its derivative regulations.